TRANSVAJİNAL MESANE BOYNU SÜSPANSİYONU VE SLİNG OPERASYONLARINDA ENDOSKOPİNİN YERİ - DEMİRKESEN, Oktay; ÇETİNEL, Bülent; YAYCIOĞLU, Özgür; TÜFEK, İlter; İSMAİLOĞLU, Vasif; SOLOK, Vural (Cerrahpaşa Medical Journal, 2014)
Background and Design.-We retrospectively reviewed the records of 68 female patients who underwent either Pubovaginal Sling (PVS) or Modified Raz "Anterior Vaginal Wall Sling (AVWS) operations between December 1993 and March 1999, in order to determine the role and importance of endoscopic controls during transvaginal bladder neck suspension and sling operations for stress urinary incontinence. AVWS was performed in 22 and PVS in 46 patients. Endoscopic controls were performed before the sutures were tied over the rectus fascia. Bladder wall, bladder neck and the position of the balloon of the cystostomy catheter were examined and the ureters were catheterized in order to ensure that no ureteric injury occurred. Results.Bladder neck perforation was detected in 2 patients and repaired accordingly. In 2 patients ureteric entrapment by the sutures was detected and the sutures were replaced. In 1 patient the balloon of the cystostomy catheter was found outside the bladder and the catheter was reinserted. One patient, whose cystostomy catheter was not controlled during cystoscopy, developed severe suprapubic pain postoperatively, on reexamination it was found that the balloon of the cystostomy catheter was placed outside the bladder. Inadequate drainage of the bladder during the operation was responsible for the injury in one of the 2 patients who suffered bladder neck perforation. Concomitant cystocele repair was performed in both of the patients whose ureters were entrapped. Conclusion.Concomitant cystocele repair and inadequate bladder drainage are factors that increase the risk of intraoperative complications. Endoscopic control is mandatory in sling and transvaginal suspension operations for early recognition and appropriate repair of such complications.